Influence of KCl and HCl on a laser clad FeCrAl alloy: In-Situ SEM and controlled environment High temperature corrosion. (September 2019) - Reddy, L.; Sattari, M.; Davis, C.J.; Shipway, P.H.; Halvarsson, M.; Hussain, T.
Highlights: In-situ ESEM with KCl was carried out on the FeCrAl laser clad at 450 °C for 1 h. An iron rich oxide, an iron-chromium mixed oxide and an aluminium enriched layer were found in TEM. In furnace tests, HCl allowed chlorine based corrosion to occur which suggests gas phase interaction. The mass gain in HCl with KCl was significantly lower than that observed in air with KCl. Abstract: This study investigated the effects of HCl and KCl on a laser-clad FeCrAl coating at 450 °C in an in-situ ESEM followed by a furnace exposure. In all in-situ TEM cross-sections, three major phases were identified: an iron rich oxide, an iron-chromium mixed oxide and an aluminium enriched layer. HCl allowed chlorine based corrosion to occur which suggests interaction from its gas phase. EDX of the regions around KCl crystals showed a decrease in chromium which is an indication of chlorine selectively removing chromium. Moreover, the mass gain in HCl with KCl was significantly lower than that observed in air with KCl.